Plausible Applicability of Aqueous Congo Red Dye System as Secondary Gamma-ray Dosimeter - I. Das Sarma; D. V. Parwate (E-Journal of Chemistry)
Aqueous congo red dye solutions in the concentration range of 0.01–0.03mM were irradiated for varying γ doses 0.050 kGy to 0.150 kGy. The molar extinction coefficient of the dye solution of congo red was found to be 2.70×105 at its absorption maxima 499.0 nm. No change in λmax was observed on irradiation. As the dye solutions are sensitive towards γ–irradiation, decolouration occurs on irradiation. The G–values for the doses in between the range of 0.035 kGy to 0.125 kGy were found to be practically constant for pure aqueous systems. Hence this was used to determine the dose of the gamma source. With the addition of alcohols in the systems, degradation of the dyes due to radiations decreased considerably.